THE COVID-19 PANDEMIC AND THE WORLD OF WORK CONTRADICTIONS - AN ANALYSIS OF EMERGING COUNTRIES, THE CASE OF BRAZIL - Menezes, Daniel Francisco Nagao; Contipelli, Ernani (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2025)
The goal of this study was to analyze how the COVID-19 pandemic is related with existing contradictions in the world of contemporary work, bringing them to light in a moment of collective vulnerability, triggered by social and economic fractures. The understanding of these relationships can contribute to the COVID-19 psychosocial impact investigation in our society. In addition, it can elucidate fruitful paths to understand the dynamics of psychological suffering related to professional categories that evidence a leading role in combating the pandemic. The adopted methodology was the hypothetical deductive one, using the literature review.